CHARGED HADRON COMPOSITION OF THE FINAL-STATE IN E+E- ANNIHILATION AT HIGH-ENERGIES - Althoff, M; Brandelik, R; Braunschweig, W; Gather, K; Kirschfink, F; Lubelsmeyer, K; Martyn, H; Peise, G; Rimkus, J; Sander, H; Schmitz, D; Siebke, H; et al. (Springer-Verlag, 1983)
The inclusive production of π± and K± mesons and of protons and antiprotons in e+e- annihilation has been measured at c.m. energies of W=14, 22 and 34GeV. Using time of flight measurements and Cerenkov counters the full momentum range has been covered. Differential cross sections and total particle yields are given. At particle momenta of 0.4 GeV/c more than 90% of the charged hadrons are pions. With increasing momentum the fraction of pions among the charged hadrons decreases. At W=34 GeV and a momentum of 5 GeV/c the particle fractions are approximately π±:K±:p, Mathematical expression. On average an event at W=34 GeV contains 10.3±0.4π±, 2.0±0.2 K± and 0.8±0.1 p, Mathematical expression. In addition, we present results on baryon correlations using a sample of events where two or more protons and/or antiprotons are observed in the final state. © 1983 Springer-Verlag.